Beyond Window Dressing: Does Moving to a New Building Really Shape the Perception of, and Actual Safety on Forensic Inpatient Programs?. Issue 3 (27th August 2021) - Bridekirk, Jonathan; Ham, Elke; Ball, Laura C.; Konkolÿ Thege, Barna
Abstract: Waypoint Centre for Mental Health Care expanded its facility in 2014 to include a new state-of-the-art forensic hospital building, called the Atrium. Prior to moving Waypoint's forensic programs into the Atrium, the Therapeutic Climate Study (TCS) was launched in order to monitor changes in perceived and objective safety indicators among forensic staff and patients. The present study consisted of a 5-year cross-sectional sequential design, consisting of both survey and hospital administrative data. Across all years of data collection, inpatients ( N total = 256) reported higher perceived safety when compared to staff ( N total = 932). However, changes in perceived safety were not linear and only slightly improved for staff over time. Sociodemographic characteristics and perceived recovery measures predicted perceived safety for staff and inpatients, regardless of the move. Male staff reported higher perceived quality of patient-service provider relationships and lower perceived safety, whereas female staff reported higher perceived patient cohesion and higher perceived safety. Both staff and inpatients who perceived the hospital's principles and practices as more recovery-oriented reported higher perceived safety. Inpatients who have been at the hospital longer reported lower perceived safety, regardless of the move. Hospital administrative data showed the number of incidents in a centralized emergency response system spiked right after the move but eventually tapered off, whereas the rates of violent incidents had increased and remained higher since moving to the new building. Results from this study suggest that staffs' and inpatients' sense of safety is determined by multiple factors, of which physical environment seems to play a less central role.